HOW DOES POVERTY AFFECT MIGRATION PATTERNS, AND HOW CAN POLICYMAKERS ADDRESS POVERTY-RELATED MIGRATION ISSUES IN WAYS THAT ARE EQUITABLE AND EFFECTIVE - Irshad Ahmad Reshi; Dr M Rajeswari (CV. Radja Publika, 2021)
Poverty and migration are two intertwined concepts that have significant implications for both developed and developing countries. The phenomenon of migration is often seen as a consequence of poverty, as individuals and families seek better economic opportunities and living conditions elsewhere. This research article aims to examine how poverty affects migration patterns and how policymakers can address poverty-related migration issues in ways that are equitable and effective. The study will draw on existing literature and empirical evidence to highlight the complex relationship between poverty and migration, and the policy implications of this relationship.